Forage production and perennial root biomass in alfalfa under two cutting heights - Blain, Gabriel; Assuero, Silvia Graciela; Berone, German Dario (Ediciones INTA, 2023)
This study evaluated the impact of cutting severity (4 vs. 10 cm cutting height) on forage production and biomass of perennial organs (root plus crown), in two contrasting winter dormant cultivars of lucerne (G6 vs. G10), defoliated more frequently than usually recommended, during the first year of life. The experiment was conducted in outdoor pots, under non-limiting water and nutritional conditions. Between November 5, 2014 and September 2, 2015, plants were cut approximately every 370 growing degree days (GDD) at the 4 and 10 cm in height. No differences were ob served between cultivars. Forage yield (biomass harvested above cutting height) was similar between plants cut at 10 and 4 cm in height. Plants cut at 10 cm in height showed higher perennial biomass than those cut at 4 cm. At the same time, plants cut at 10 cm quickly achieved perennial biomass levels higher than 3000 kg DM/ha, a value at which it is considered that partitioning to roots would not limit the aerial biomass production. Consequently, a management of defoliation that contemplates a higher post-cut foliar residual allows to reconcile the need for early use of lucerne pastures with the need to establish a vigorous perennial system during the year of establishment.